The international legal framework for child soldiers. Evolution and new debates after the Ongwen case before the International Criminal Court - Rodríguez Rodríguez, Jorge (2021)
The situation of child soldiers is undoubtedly one of the most dangerous contexts within the international community. Despite the broadness of international regulation in this area (International Humanitarian Law, International Human Rights Law or International Criminal Law), we still find certainly alarming figures that should be interpreted as a warning for States to redouble their efforts in order to eradicate any participation of childs in armed conflicts. This article analyses the international standards in this area from the 1977 Additional Protocols to the Convention on the Rights of the Child and its Optional Protocol on the involvement of children in armed conflict. In addition, the article studies the Rome Statute and the jurisprudence of the International Criminal Court. Also, it focuses especially on the debates on the judgment on Dominic Ongwen, a former child soldier.